If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4(3x + 2) = 19 Reorder the terms: 3x + -4(2 + 3x) = 19 3x + (2 * -4 + 3x * -4) = 19 3x + (-8 + -12x) = 19 Reorder the terms: -8 + 3x + -12x = 19 Combine like terms: 3x + -12x = -9x -8 + -9x = 19 Solving -8 + -9x = 19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -9x = 19 + 8 Combine like terms: -8 + 8 = 0 0 + -9x = 19 + 8 -9x = 19 + 8 Combine like terms: 19 + 8 = 27 -9x = 27 Divide each side by '-9'. x = -3 Simplifying x = -3
| 2(5x+3)-10=2(3x+12) | | 3=x-19 | | 6x-3(2x+1)=12 | | 15+17=13t-14 | | 16t^2+276t=0 | | 8=33+y | | 8a-5=-3 | | -3/2-5/4y=3/8 | | -46+x=25 | | k/4+5 | | 3x+8x-(7x+5)= | | 3(5j+2)-j=2(j-3) | | -9/2x-9/7=-9/5 | | -1.68+1.24=13 | | 5y/12+y/14 | | 6+x/4=10 | | -1/3=-1/4u+1/2 | | m/3-8/5 | | y=-11x | | 2X+15-X=20 | | 21x+9-6x-2= | | m/3=m/12+3/4 | | .5=4.1h-2(1.3h-4) | | m+4/6 | | 4(2m-3)+m=-3 | | -4/7x=3/14-9/14 | | x+3(2-x)=6-2x | | -13+16-2+(-20)= | | 4(5x+9)=-2(x+7) | | 2(v-3)=2v+8-4(-4v-1) | | x-3(2-x)=6-2x | | 13*175=13*90+85*13 |